COMPACTION OF LOESS BASES OF BUILDINGS AND STRUCTURES, AS WELL AS BULK SOILS AROUND THE FOUNDATION USING VIBRATORY ROLLERS IN SEISMIC AREAS - Khakimov G. A.; Samiyeva Sh. Kh.; Muminov A.A.; Berdimurodov A.E.; Muminov J.A. (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article discusses the sequence of the process of compaction of loess foundations of buildings and bulk soils around the foundation in seismic areas, using vibratory rollers. The recommendation on vibration compaction of loess bases of buildings and bulk soils around the foundation in seismic areas is given. These recommendations can be used to increase the density and associated strength indicators of moistened loess soils lying within the compressible thickness of the base, the value of which does not exceed 2.0-3.0 m, as well as for bulk soils layered around the foundation.The developed recommendations on vibration compaction of foundations and bulk soils around the foundation give a good result in the plan under consideration for structures characterized by a load intensity up to P = 0.15-0.20 MPa. It should be noted that in the conditions of Central Asia, in particular Uzbekistan, where additional deformations (seismic subsidence) may occur in the foundations and around the foundations of buildings and structures, the method of compaction of soils using vibratory rollers is the most reliable way to prepare the foundations of buildings and structures.